Penyuluhan Dagusibu Sebagai Upaya Meningkatkan Pengetahuan Siswa SMP Tentang Penyimpanan Obat Berdasarkan Bentuk Sediaan - Hindri Syahputri; Yusnita Putri Marpaung; Zahrima Dwi Ananda Lubis; Nadia Pasaribu; Putri Aulia; Khoirul Ummi Nur’ailah Surbakti (Journal Of Human And Education (JAHE), 2026)
Improper medication storage can compromise a drug's quality, stability, safety, and effectiveness, potentially diminishing its therapeutic benefits. Therefore, early education on the proper acquisition, use, storage, and disposal of medicines—specifically through the DAGUSIBU program (an acronym for *Dapatkan, Gunakan, Simpan, dan Buang Obat dengan Benar* or "Obtain, Use, Store, and Dispose of Medicines Correctly")—is essential. This community service initiative aimed to enhance the knowledge of junior high school students regarding medication storage based on dosage forms. The activity employed interactive educational methods, including presentations, leaflet distribution, discussions, Q&A sessions, and quizzes to evaluate participant understanding. Conducted as part of the Student Community Service (KKN) program, the initiative targeted junior high school students as its primary audience. The results demonstrated that participants engaged enthusiastically, actively contributed to discussions, and successfully answered questions during the evaluation session. This educational effort is expected to improve students' knowledge and awareness of proper medication storage, enabling them to apply these practices in their daily lives and promote rational medication use within their families and communities